Estrogenic Activity of Glycitein, a Soy Isoflavone - Tong T. Song; Suzanne Hendrich; Patricia A. Murphy (2002)
ADVERTISEMENT RETURN TO ISSUEPREVAddition/CorrectionORIGINAL ARTICLEThis notice is a correctionEstrogenic Activity of Glycitein, a Soy IsoflavoneTong T. Song, Suzanne Hendrich, and Patricia A. MurphyCite this: J. Agric. Food Chem. 2002, 50, 8, 2470Publication Date (Web):March 13, 2002Publication History Published online13 March 2002Published inissue 1 April 2002https://pubs.acs.org/doi/10.1021/jf020260vhttps://doi.org/10.1021/jf020260vcorrectionACS PublicationsCopyright © 2002 American Chemical Society. This publication is available under these Terms of Use. Request reuse permissions This publication is free to access through this site. Learn MoreArticle Views407Altmetric-Citations4LEARN ABOUT THESE METRICSArticle Views are the COUNTER-compliant sum of full text article downloads since November 2008 (both PDF and HTML) across all institutions and individuals. These metrics are regularly updated to reflect usage leading up to the last few days.Citations are the number of other articles citing this article, calculated by Crossref and updated daily. Find more information about Crossref citation counts.The Altmetric Attention Score is a quantitative measure of the attention that a research article has received online. Clicking on the donut icon will load a page at altmetric.com with additional details about the score and the social media presence for the given article. Find more information on the Altmetric Attention Score and how the score is calculated. Share Add toView InAdd Full Text with ReferenceAdd Description ExportRISCitationCitation and abstractCitation and referencesMore Options Share onFacebookTwitterWechatLinked InRedditEmail PDF (10 KB) Get e-Alertsclose Get e-Alerts